Anwāʿu al-Naʿt wa Aghrāḍuhu fī Kitāb Durūs al-Lughah al-ʿArabiyyah li Imām Zarkashiy wa Imām Syubbāniy - Suryadarma, Yoke; Saidah, Mandrasi Amira; Yolanda, Fidela Devi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The book